Microeconomics / Second Edition - Perloff Jeffrey M (Addison-Wesley Publishing Company, 2001)
Preface, Introduction, Supply and Demand, Applying the Supply and Demand Model, Consumer Theory, Consumer Choice, Applying Consumer Theory, Theory of the Firm, Firms and Production, Costs, Perfect Competition, Competitive Firms and Markets, Applying the Competitive Model, General Equilibrium and Economic Welfare, Market Power and Market Structure, Monopoly, Pricing, Oligopoly and Monopolistic Competition, Strategy, Factor Markets, Factor Markets and Vertical Integration, Interest Rates and Investments and Capital Markets, Uncertainty and Missing Markets and Limited Information, Uncertainty, Externalities and Commons and Public Goods, Asymetric Information, Contracts and Moral Hazards, Appendices, References, Index.